Challenges Faced by Working Population During Lockdown in Response to Corona Virus Outbreak - 1 Sonopant G Joshi, Sheetal Barde2 , Ranjana Chavan2 , Deepali Dumbre3 , Tejashree Ligade3 , Roma Sh (Indian Journal of Forensic Medicine & Toxicology, 2020)
COVID-19 pandemic has created an unprecedented social and health challenges on the working-classpopulation in India and across the globe. To mitigate the spread of the virus all the state and centralgovernment in India imposed lockdown in the society over the weeks or, in some cases months. Thislockdown has made a severe impact on the physical, psychological, financial, and social conditions of thepeople. The aim of this study is to understand the impact of lockdown amongst people on their personal life,work life and health conditions. Independent survey was conducted to collect the descriptive statistics from120 participants. Majority of the participants expressed that their life become difficult in lockdown. Thereis big challenge observed for women to manage children under 10 years of age. Work from home patternwas found favourable for those who are using computer and internet. Many participants were stressful andfearful as their job is at stake due to heavy financial loss to their employing organization. We have appliedchi square test to find out association and it was found that age and gender is not significantly associated withfacing challenges while other demographic factors are significantly associated.